2022
DOI: 10.1017/s003329172200006x
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory curves of post-COVID anxiety/depressive symptoms and sleep quality in previously hospitalized COVID-19 survivors: the LONG-COVID-EXP-CM multicenter study

Abstract: Pellicer-Valero OJ (2023). Trajectory curves of post-COVID anxiety/depressive symptoms and sleep quality in previously hospitalized COVID-19 survivors: the LONG-COVID-EXP-CM multicenter study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…The two surveys reported different sequelae, and hence were regarded as two independent studies and included in the meta-analysis, while data on cough was included from the telephone follow-up only. Four articles which included one same cohort were included in the meta-analysis as four independent studies as they reported different symptoms [ 21 24 ]. The average follow-up time ranged from 90 days to 13.2 months and the size of follow-up cohorts ranged from 101 to 47,780.…”
Section: Resultsmentioning
confidence: 99%
“…The two surveys reported different sequelae, and hence were regarded as two independent studies and included in the meta-analysis, while data on cough was included from the telephone follow-up only. Four articles which included one same cohort were included in the meta-analysis as four independent studies as they reported different symptoms [ 21 24 ]. The average follow-up time ranged from 90 days to 13.2 months and the size of follow-up cohorts ranged from 101 to 47,780.…”
Section: Resultsmentioning
confidence: 99%
“…However, we did find associations between poor sleep and subsequent long COVID. Whilst sleep disturbances have been commonly reported in people suffering from long COVID [31,32], to our knowledge this is the first study to examine pre-infection sleep quality in relation to long COVID development. Lack of sleep can compromise both innate and adaptive immune function, making individuals more susceptible infectious disease, and reduce the effectiveness of vaccine response [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, Saunders et al observed that most individuals with anxiety or depression symptoms evolved positively during the first week after the COVID-19 lockdown [ 39 ]. The only study investigating the longitudinal evolution of anxiety and depressive symptoms in subjects with long COVID found that post-COVID anxiety and depressive symptoms tended to slowly recover during the following five years after the SARS-CoV-2 infection [ 40 ]. Finally, it is important to consider limitations related to the methodological design of the study.…”
Section: Discussionmentioning
confidence: 99%